Pencils of Euler Triples, I - Čerin, Zvonko (Sarajevo Journal of Mathematics, 2024)
In this paper we will study the families of triples $(u,v,w)$ of elements in a commutative ring $r$ with the property that $v\,w+n=\widetilde{u}^2$, $w\,u+n=\widetilde{v}^2$ and $u\,v+n=\widetilde{w}^2$ for some $n, ... 2000 Mathematics Subject Classification. Primary 11B37, 11B39, 11D09